DEMAND, ABILITY TO PAY FOR COVID-19 VACCINE AND ASSOCIATED FACTORS OF HANOI MEDICAL UNIVERSITY STUDENTS IN 2020 (Tạp chí Y học Cộng đồng, 2022)
Background: The development of a vaccine against COVID-19 infection is on the way.However, opinions on the implementation of the vaccine and the needs to receive theCOVID-19 vaccine vary considerably among people, which might influence the futuredemand forecast and pricing considerations for COVID-19 vaccine. Objectives: Thisstudy aims at 1) describing the demand and ability to pay, and 2) analysing factorsassociated with participants; intention to utilize the COVID-19 vaccine of medicalstudents. Subjects and methods: We conducted a cross-sectional study among HanoiMedical University students. Logistic regression was used to describe the correlationbetween COVID-19 vaccination needs and related factors. Linear regression wasused to describe the correlation between the ability to pay for the COVID-19 vaccineand some associated factors. Results: Nearly 80% of the participants reported thatthey were willing to get vaccinated against COVID-19 if a vaccine were available.Factors associated with students’ needs to accept the COVID-19 vaccine includedworry about COVID-19 and the year of study of participants. The average price thatpeople accept to pay for a vaccine against COVID-19 is 485.25 ± 418.64 thousandVND. Conclusion: In this study, many students aaalikely get vaccinated, and theneed to uptake COVID-19 vaccine was considered to be associated with worry ofCOVID-19 and year of study.
Keywords: COVID-19 vaccine, demand, intention, ability to pay.